Appraisal of Urban Trees Value Using Thyer Method - Fazilah Musa; Awang Noor, A. G.; Mustafa Kamal, M. S.; Abdullah, M. (Universiti Putra Malaysia Press, 2013)
Urban tree-planting provides not only environmental benefits, but it also has significant value both socially and economically. Unfortunately, the economic benefits of urban trees are difficult to estimate due to the absence of a well-defined market. A range of methods have been developed to estimate the economic value of urban trees. Hence, this study attempted to appraise the value of urban trees in Kuala Lumpur using the Thyer method. Five hundred and three trees were selected upon consultation with Kuala Lumpur City Hall, and this was followed by field observations, which were carried out with the aim to document tree species, age, circumference, height, crown diameter and tree characteristics. Results indicated that Pterocarpus indicus has the highest value, with an estimated mean tree value of RM972,660. Meanwhile, the mean value per tree was estimated at RM435,851. However, the value of urban trees differs with respect to the physical and qualitative characteristics of the tree.